Temporary faecal diversion in ileocolic resection for Crohn's disease: is there an impact on long‐term surgical recurrence?. (10th December 2019) - Bolckmans, R.; Singh, S.; Ratnatunga, K.; Wickramasinghe, D.; Sahnan, K.; Adegbola, S.; Kalman, D.; Jones, H.; Travis, S.; Warusavitarne, J.; Myrelid, P.; George, B.
Abstract: Aim: Temporary faecal diversion after ileocolic resection (ICR) for Crohn's disease reduces postoperative anastomotic complications in high‐risk patients. The aim of this study was to assess if this approach also reduces long‐term surgical recurrence. Method: This was a multicentre retrospective review of prospectively maintained databases. Patient demographics, medical and surgical details were collected by three specialist centres. All patients had undergone an ICR between 2000 and 2012. The primary end‐point was surgical recurrence. Results: Three hundred and twelve patients (80%) underwent an ICR without covering ileostomy (one stage). Seventy‐seven (20%) had undergone an ICR with end ileostomy/double‐barrel ileostomy/enterocolostomy followed by closure (two stage). The median follow‐up was 105 months [interquartile range (IQR) 76–136 months]. The median time to ileostomy closure was 9 months (IQR 5–12 months). There was no significant difference in surgical recurrence between the one‐ and two‐stage groups (18% vs 16%, P = 0.94). We noted that smokers (20% vs 34%, P = 0.01) and patients with penetrating disease (28% vs 52%, P < 0.01) were more likely to be defunctioned. A reduced recurrence rate was observed in the small high‐risk group of patients who were smokers with penetrating disease behaviour treated with a two‐stage strategy (0/10 vs 4/7, P = 0.12). Conclusion: Despite having higher baseline risk factors, the results in terms of rate of surgical recurrence over 9 years are similar for patients having a two‐stage compared with a one‐stage procedure.